Phylogenetic Analysis of the Mpox Virus in Sub-Saharan Africa (2022–2024) - Millicent Ochieng; Daniel Kiboi; Carolyne Nasimiyu; Eric Osoro; Dorcus C. A. Omoga; Josiah O. Kuja (Biology, 2025)
Mpox, caused by the Mpox virus (MPXV), is a re-emerging zoonotic disease in the Poxviridae family. Since 2022, sub-Saharan Africa has experienced recurrent outbreaks, with the Democratic Republic of the Congo (DRC) accounting for 96% of the 567 confirmed cases reported in the African region by the World Health Organization as of June 2024. Despite MPXV’s endemic presence, its genomic diversity and evolutionary dynamics remain poorly characterized. We analyzed 270 MPXV genomes from 13 sub-Saharan African countries (2022–2024), representing the most geographically comprehensive regional dataset from the outbreak period. Phylogenetic analysis identified two geographically distinct clades: Clade I (East/Central Africa) and Clade II (West/Southern Africa). A marked disparity in APOBEC3-associated mutations was observed, with Clade IIb exhibiting significantly higher enrichment than Clade I, suggesting clade-specific host adaptation pressures. These mutations predominantly target genes involved in immune evasion and replication. Preliminary functional predictions indicated that selected missense mutations may impact on protein stability, underscoring the need for further experimental validation. Our findings provide the first pan–sub-Saharan analysis of MPXV clade divergence and reinforce the importance of sustained, regionally informed genomic surveillance to monitor viral evolution and guide outbreak response strategies across Africa.